no clue!
2006-11-20 02:55:36
·
answer #1
·
answered by dodd319 4
·
0⤊
1⤋
Put x^2+4x+2=4
this gives x= -2+root 6
-2-root 6
2006-11-20 10:52:27
·
answer #2
·
answered by promy 1
·
0⤊
0⤋
This is too simple,
You know, f(x) should be equivalent to 4:
f(x)=4
Putting f(x)'s condition to the equation above:
-x^2 + 4x + 2 = 4
Adding (-4) to both sides of the equation:
-x^2 + 4x -2 = 0
By solving this equation for x, you will find the answer(s).
2006-11-20 10:54:56
·
answer #3
·
answered by Babax 3
·
0⤊
0⤋
using the pemdas (parentesis, exponents, multication*, division*, add* and subtract*)
*going left to right in the problem which ever operation is first
-x^2+4x+2 (x = 4)
-4^2+4(4)+2
-16+16+2
-34
thats what i get but i could be wrong
2006-11-20 11:04:33
·
answer #4
·
answered by jamz 5
·
0⤊
0⤋
f(x) = 4
-x^2+4x+2 = 4
-x^2+4x+2 - 4 = 0
-x^2+4x- 2 = 0
Use ABC....
x = 3,414 AND x = 0,586
2006-11-20 11:00:12
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
f(x) = x^2+4x+2 = 4
if (x^2+4x+4) = 6 ( by adding 2 on both sides to make it square)
if(x+2)^2 = 6
if x +2 = +/- sqrt(6)
if x= - 2+ sqrt(6) or -2- sqrt(6)
2006-11-20 10:54:32
·
answer #6
·
answered by Mein Hoon Na 7
·
0⤊
0⤋
put f(x)= 4
4= x^2+4x+2
x^2+4x=2
x^2+4x-2=0
simplify!!
2006-11-20 10:51:45
·
answer #7
·
answered by Ankit B 4
·
0⤊
0⤋
x^2+4x+2=4 => x^2+4x-2=0
delta=16+8=24=(2sqrt(6))^2
x1=(-4-2sqrt(6))/2=-2-sqrt(6)
x2=(-4+2sqrt(6))/2=-2+sqrt(6)
2006-11-20 10:53:50
·
answer #8
·
answered by Iulia-Diana 2
·
0⤊
0⤋
i used to know how to do that stuff
but i forgot over the summer haha
sorry
2006-11-20 10:47:41
·
answer #9
·
answered by samantha 2
·
0⤊
1⤋